Prayer and Personality Formation: Psychological Review - Teguh Saputra; Muhtar Sholihin (Gunung Djati Conference Series, 2021)
This study aims to discuss prayer and personality formation based on a psychological review. This research method uses qualitative research through literature study and interpretation approach with primary sources, namely the book of interpretation of Al-Azhar by Buya Hamka and secondary sources, namely theses, theses, dissertations and journals related to this research. Then this study applies content analysis as a tool to explore the collected data so that it can lead to conclusions. The results and discussion of this study include personality in the perspective of Islamic psychology, prayer in Buya Hamka's interpretation of Al-Azhar and analysis of prayer and personality formation in Buya Hamka's interpretation of Al-Azhar with a multidisciplinary approach in the form of psychology. This study concludes that prayer contains the values ​​of moral education in the form of prayer that can foster awareness, commitment, discipline, responsibility and dhikrullah, namely always remembering Allah SWT. So that after being embedded in someone's dhikrullah will grow an attitude of guarding and maintaining themselves by doing His commands and staying away from His prohibitions. Until in the end, a muttaqin personality will be born in a person as a result of always establishing prayers correctly, solemnly and applying the values ​​of moral education contained in praying in daily life